Biodiversity and Urban Gardens: Medicinal and Aromatic Plants That Can Used In Erzurum (Turkey) Urban Gardens - İşik Sezen; Neslihan Demi̇rcan; Esen Sezen Karaoğlan (Journal of Architectural Sciences and Applications, 2018)
AbstractTurkey is a rich country in biodiversity due to its characteristics like topographic and geomorphological structures it shelters, being an extended peninsula and climatic features. Europe and Middle East countries with the richest biodiversity distribution showing the number of plant species in Turkey is close to the number of plant species in the whole of the European continent.According to data of TUBIVES 2017 (official plant database), Turkey owns more than 12000 plant taxa 3000 of which are endemic. Erzurum province shelters 264 of endemic plants growing in East Anatolia, some of which have medicinal and aromatic effects East Anatolia Region of Turkey is the second richest region in the country following the Mediterranean for the number of endemic plant species.